Measurement of the complete core plasma flow across the LOC–SOC transition at ASDEX Upgrade. (20th December 2017) - Lebschy, A.; McDermott, R.M.; Angioni, C.; Geiger, B.; Prisiazhniuk, D.; Cavedon, M.; Conway, G.D.; Dux, R.; Dunne, M.G.; Kappatou, A.; Pütterich, T.; Stroth, U.; et al.
Abstract: A newly installed core charge exchange recombination spectroscopy (CXRS) diagnostic at ASDEX Upgrade (AUG) enables the evaluation of the core poloidal rotation ( u p o l ) through the inboard-outboard asymmetry of the toroidal rotation with an accuracy of 0.5 to 1 km s − 1 . Using this technique, the total plasma flow has been measured in Ohmic L-mode plasmas across the transition from the linear to saturated ohmic confinement (LOC–SOC) regimes. The core poloidal rotation of the plasma around mid-radius is found to be always in the ion diamagnetic direction, in disagreement with neoclassical (NC) predictions. The edge rotation is found to be electron-directed and consistent with NC codes. This measurement provides as well the missing ingredient to evaluate the core E → × B → velocity ( u E → × B → ) from data only, which can then be compared to measurements of the perpendicular velocity of the turbulent fluctuations ( u ⊥ ) to gain information on the turbulent phase velocity ( v p h ). The non neoclassical u p o l from CXRS leads to good agreement between u E → × B → and u ⊥ indicating that v p h is small and at similar values as found with gyrokinetic simulations. Moreover, the data shows a shift of v p h in the ion-diamagnetic direction at the edge after the transition from LOC to SOC consistent with a change in the dominant turbulence regime. The upgrade of the core CXRS system provides as well a deeper insight into the intrinsic rotation. This paper shows that the reversal of the core toroidal rotation occurs clearly after the LOC–SOC transition and concomitant with the peaking of the electron density.